Pre-school children's literacy development in the Kazakh home learning environment - Zhakim, Assel (Journal of Education and e-Learning Research, 2024)
The home environment and experiences before a child enters formal schooling have a significant impact on their educational progress and results. Most research in this area has been conducted in Western countries and may differ across different countries and cultures. The purpose of this study is to investigate how literacy skills are developed in Kazakh homes and the kinds of social interactions that take place between parents and children to foster this development. An ethnographic case study design through participant observations and interviews was used to further understand the relationship between the Kazakh home learning environment (HLE) and literacy development in four affluent and highly educated families. The findings of this study suggest that parent-child social interactions play an important role in the development of literacy skills in Kazakh families. The parents purposefully used play, joint book reading and storytelling to focus on oral language development and to establish skills in one language first despite the fact that Kazakhstan is a bilingual country that is gradually moving towards a trilingual policy (Kazakh, Russian and English). The study highlights the types of regular and high-quality literacy-related social interactions parents engage in to help their children succeed educationally in school and beyond. The findings of this study suggest that children would benefit from regular parent-child interactions and policymakers and other stakeholders responsible for early years learning and development should encourage parents to be actively involved in their children's learning and literacy development in the home environment.